Esophageal Varices after Interopsed Esophagojejunostomi-A Report of Two Cases - Hashimoto, Naoki; Fukuda, Masaharu; Terakata, Souichi; Ashida, Hiroshi; Nishioka, Akihiko; Ishikawa, Yoshio; Utsunomiya, Jouji; Takagi, Kazumitsu (Nippon Shokaki Geka Gakkai zasshi, 1990)
We describe two patients with bleeding esophageal varices who underwent proximal gastrectomy and interposed esophagojejunostomy. The first patient is 63-year-old man who had those procedures because of a bleeding E-G junctional ulcer and had been given a blood transfusion 14 years earlier. The second patient is a 55-year-old woman with idiopathic portal hypertension who underwent the abovementioned procedure for remnant gastric carcinoid and recurrent esophageal varices 4 years earlier. These esophageal varices were eradicated by several sessions of endoscopic sclerotherpay. To date, no bleeding has reccured in 6 months. The abdominal angiographic studies in these two cases revealed, in the second case, some collaterals between the esophageal varices and the enlarged venous system of the interposed jejunum and, in the first case, there were no such collaterals only an enlarged marginal vein of the interposed jujunum. The regional hyperdynamic state in the interposed jejunum might have caused the esophageal varices in the first case.